Decavanadate interactions with actin: cysteine oxidation and vanadyl formation - Ramos, Susana (2012)
Incubation of actin with decavanadate induces cysteine oxidation and oxidovanadium(IV) formation. The studies were performed combining kinetic with spectroscopic (NMR and EPR) methodologies. Although decavanadate is converted to labile oxovanadates, the rate of deoligomerization can be very slow (half-life time of 5.4 h, at 25 ◦C, with a first order kinetics), which effectively allows decavanadate to exist for some time under experimental conditions. It was observed that decavanadate inhibits F-actin-stimulated myosin ATPase activity with an IC50 of 0.8 mMV10 species, whereas 50 mMof vanadate or oxidovanadium(IV) only inhibits enzyme activity up to 25%. Moreover, from these three vanadium forms, only decavanadate induces the oxidation of the so called “fast” cysteines (or exposed cysteine, Cys-374) when the enzyme is in the polymerized and active form, F-actin, with an IC50 of 1 mMV10 species. Decavanadate exposition to F- and G-actin (monomeric form) promotes vanadate reduction since a typical EPR oxidovanadium(IV) spectrum was observed. Upon observation that V10 reduces to oxidovanadium(IV), it is proposed that this cation interacts with G-actin (Kd of 7.48 ± 1.11 mM), and with F-actin (Kd = 43.05 ± 5.34 mM) with 1:1 and 4:1 stoichiometries, respectively, as observed by EPR upon protein titration with oxidovanadium(IV). The interaction of oxidovanadium(IV) with the protein may occur close to the ATP binding site of actin, eventually with lysine-336 and 3 water molecules.